MANAJEMEN PAKAN PEDET PADA PETERNAKAN SAPI PERAH DI UNIT PELAKSANA TEKNIS DAERAH BALAI PENGEMBANGAN BIBIT PAKAN TERNAK DAN DIAGNOSTIK KEHEWANAN DAERAH ISTIMEWA YOGYAKARTA - , FAGOLODODO DUHA, drh. Guntari Titik Mulyani, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The practice of field work aims to gain the skills and work experience in the field of animal husbandry and animal health management in particular calf feed dairy cows. The practice of field work was carried on March 7 up to March 11, 2014 at a dairy farm in Implementing Regional Technical Center for the development of livestock feed and Seed Animals Diagnostic (UPTD-BPBPTDK), Sleman, Yogyakarta. The basic methods used in practice this field work is the collection of information by conducting interviews with officers and direct observations of conditions and the following activities at a dairy farm in UPTD-BPBPTDK, Sleman, Yogyakarta to feed calf management of dairy cows. Result of the calf dairy cows feed management obtained during field work practice to follow is calf in UPTD-BPBPTDK totalling 4 tail calf and have a different age ranging from 6 days up to age 4 month, and consists of 2 tail males calf and 2 tail calf females. The average birth weight 34-43 kg. The calf 1-4 days given colostrum 1.5-2 liters everydays